Analisis Tingkat Profitabilitas Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 (Studi Kasus Pt Activity Based Management Investama Tbk) - Suardi, Suardi; Yuliana, Yuliana (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2024)
The main problem in this research is to determine the level of profitability of companies listed on the Indonesia Stock Exchange during the period 2018-2022 (Case Study: PT ABM Investama Tbk). This study aims to determine the level of profitability of PT ABM Investama Tbk. The research method employed in this study is descriptive quantitative method. The data analysis in this research utilizes Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The research findings based on the calculations indicate that the Gross Profit Margin in 2018 amounted to 23%, in 2019 amounted to 18%, in 2020 amounted to 17%, in 2021 amounted to 36%, and in 2022 amounted to 36%, with an overall average of 26% and an industry average of 24.90%. The Net Profit Margin in 2018 was 9%, in 2019 was 1%, in 2020 was 6%, in 2021 was 18%, and in 2022 was 24%, with an average ratio of 12% and an industry average ratio of 3.92%. The Return on Assets in 2018 was 8%, in 2019 was 0%, in 2020 was 5%, in 2021 was 18%, and in 2022 was 17%, with an average ratio of 10% and an industry average ratio of 5.98%. The Return on Equity in 2018 was 27%, in 2019 was 2%, in 2020 was 23%, in 2021 was 52%, and in 2022 was 55%, with an average ratio of 32% and an industry average ratio of 8.32%. Based on the calculation of profitability ratios from 2018 to 2022, PT ABM Investama Tbk experienced fluctuations